Unjust pains: the impact of COVID-19 on children in prison. Issue 4 (13th October 2020) - Bateman, Tim
Abstract : Purpose: The purpose of this paper is to consider the implications of the COVID-19 pandemic for the treatment of children in penal custody. Design/methodology/approach: This paper is a viewpoint piece that analyses the consequences of the COVID-19 pandemic for children in custody, drawing on published information where available. Findings: This paper argues that imprisoned children are an extremely vulnerable group, whose experience of incarceration exacerbates that vulnerability at the best of times. Responses to COVID-19 are particularly painful for children in those settings, and the consequences are manifestly unjust. Originality/value: This paper provides an early attempt to consider the impact of COVID-19 on children in prison.